Programa Nacional de Informática na Educação (ProInfo) e o desafio da inclusão digital : um estudo de caso do ProInfo-NTE - Niterói - Silva, Jorge Candido da (2005)
Too many actions are arising in the computer science field labeled Digital Inclusion . The Education Informatic National Program (PROINFO) is an example of that. One of the Program´s procedure is to create informatic labs at all the public schools in the whole Brazil. This dissertation will validate if the ´PROINFO´ program is really a Digital Inclusion Public Program or if it is simplely an action to create informatic places in the schools.